Sodium-ion battery positive electrode material as well as preparation method and application thereof
Through high-temperature sintering of nickel ferromanganese precursor and sodium source and the coating treatment of carbon and nitrogen and coating elements, the conductivity and stability of the positive electrode material of sodium ion battery are solved, and the ratio and circulation performance are improved to ensure that at different temperatures are Excellent performance under conditions.
Patent Information
- Application Number
- CN202411344898.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
The positive electrode material of sodium ion battery has poor conductivity, poor structural stability, poor rate performance and circulation performance, especially at low temperatures, and is susceptible to the air environment, resulting in limited development of sodium ion batteries.
Mixed sintering treatment of nickel-ferromanganese precursor, sodium source and dopant is adopted, followed by coating of carbon-nitrogen elements and coating elements to form a uniform conductive network and coating layer, improving the stability and rate performance of the material.
It significantly improves the rate performance and cycling performance of the positive electrode material of sodium ion battery, reduces the residual alkali on the surface of the material, enhances stability, and ensures excellent performance under normal temperature or low temperature conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a sodium ion battery positive electrode material and a preparation method and use thereof. Background Art
[0002] Lithium-ion batteries occupy a core position in power batteries due to their high energy density, good rate performance, and low self-discharge rate. With the rapid development of the new energy vehicle industry, lithium resources are facing a shortage of supply. Sodium, which belongs to the same main group as lithium, is becoming a beneficial supplement to lithium-ion batteries because of its similar physical and chemical properties to lithium, its abundant content in the earth's crust, and its low price. Compared with other sodium-ion positive electrode materials, sodium-ion layered materials have a relatively high theoretical specific capacity, but they have problems such as poor conductivity and poor structural stability, resulting in poor rate performance and cycle performance. At the same time, they are easily affected by the air environment, and the residual alkali of the materials is high. At low temperatures, the diffusion kinetics of sodium-ion positive electrode materials decrease, the solid electrolyte interface grows abnormally, the reaction process deteriorates, and the transmission rate of ions and electrons decreases, resulting in poor low-temperature rate performance. The above problems have seriously restricted the development of sodium-ion batteries. Summary of the invention
[0003] The purpose of the present invention is to provide a sodium ion battery positive electrode material and a preparation method and use thereof. The sodium ion battery positive electrode material provided by the present invention has high stability, low residual alkali on the material surface, high capacity, and excellent rate performance and cycle performance.
[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a positive electrode material for a sodium ion battery, wherein the method comprises: S1, mixing a nickel-iron-manganese precursor, a sodium source and a dopant to obtain a mixed material, and then performing a first sintering treatment to obtain a first powder; S2, mixing the first powder, the carbon and nitrogen source and the first solvent, performing a first heat treatment, and then performing a second sintering treatment to obtain a second powder; S3, mixing the second powder, the coating agent and the second solvent, performing a second heat treatment, and then performing a third sintering treatment to obtain a positive electrode material for a sodium ion battery.
[0005] Optionally, in step S1, the total molar ratio of the sodium element in the sodium source to (Ni+Fe+Mn) in the nickel-iron-manganese precursor is (0.90-1.09): 1; The amount of the doping element added in the dopant is 0.4-1.2wt% of the mixed material.
[0006] Optionally, in step S2, the mass ratio of the carbon-nitrogen source to the first powder is (0.001-0.02): 1; The mass ratio of the added amount of the first solvent to the first powder is (4-8):1.
[0007] Optionally, in step S3, the amount of the coating element added to the coating agent is 0.20-1.5wt% of the second powder; The mass ratio of the added amount of the second solvent to the second powder is (6-10):1.
[0008] Optionally, the sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium oxalate, sodium phosphate, sodium acetate and sodium citrate; The carbon and nitrogen source is selected from one or more of polyvinyl pyrrolidone, amides, polyaniline, dopamine and amino acids; The dopant is selected from a compound containing a doping element; the doping element is selected from one or more of Zr, Ti, Mo, Y, Ce, La, Al, W, Nb and Mg; The coating agent is selected from a compound containing a coating element; the coating element is selected from one or more of Si, Al, Ti, Mg, Ce, La, B, Co and Zr; The first solvent and the second solvent are selected from anhydrous ethanol and / or isopropanol, respectively.
[0009] Optionally, in step S1, the conditions of the first sintering treatment include: in an air or oxygen atmosphere, heating to 500-600° C. at 2-6° C. / min, then heating to 850-1100° C. at 1-4° C. / min, and sintering time is 6-16 hours; The conditions of the second sintering treatment include: a sintering temperature of 700-850° C. and a sintering time of 2-8 hours; The conditions of the third sintering treatment include: a sintering temperature of 300-700° C. and a sintering time of 4-10 hours; The second sintering process and the third sintering process are performed under an inert atmosphere, and the inert atmosphere is selected from one or more of nitrogen, argon and helium; The first heat treatment is performed in a reflux device, the temperature of the first heat treatment is 80-120° C., and the time of the first heat treatment is 0.5-8 hours; The second heat treatment is performed in a reflux device, the second heat treatment temperature is 80-120° C., and the second heat treatment time is 0.5-8 hours.
[0010] Optionally, the method further comprises, after the first sintering treatment is completed, cooling to 10-30° C. and then pulverizing and screening, wherein the D50 particle size of the first powder is 5-10 μm; After the second sintering process is completed, the second powder is crushed and sieved, and the D50 particle size of the second powder is 6-9 μm; After the third sintering process is completed, the material is crushed and sieved, and the D50 particle size of the sodium ion battery positive electrode material is 6-9 μm.
[0011] Optionally, the chemical formula of the nickel-iron-manganese precursor is as shown in formula (I): Ni a Fe b Mn c M (1-a-b-c) (OH)2(I), where 0.10≤a<1.0, b>0, c>0, 0≤1-abc≤0.15; M is selected from one or more of Mg, Co, Zn, Sr, Al, Cu, Ti, Y, La, Ce, Pr, Nd, V and Cr.
[0012] The second aspect of the present invention provides a sodium ion battery positive electrode material prepared by the method described in the first aspect of the present invention, wherein the chemical formula of the sodium ion battery positive electrode material is as shown in formula (II): Na β Ni x Fe y Mn z M (1-x-y-z) O2 (II), where 0.90≤β≤1.09, 0.10≤x<1.0, y>0, z>0, 0≤1-xyz≤0.15.
[0013] The third aspect of the present invention provides use of the sodium ion battery positive electrode material described in the second aspect of the present invention in a sodium ion battery.
[0014] Through the above technical scheme, the present invention obtains a first powder by mixing a nickel-iron-manganese precursor, a sodium source and a dopant, and then sintering the mixture at high temperature, and then coating the carbon-nitrogen element and the coating element respectively. The coating of the carbon element in the method provided by the present invention can form a uniform conductive network on the surface of the material, so that the rate performance of the material is improved, and can also suppress the volume change of the material during the charge and discharge process to a certain extent, improve the stability of the material, and the nitrogen element contained in the carbon coating layer can stabilize the unstable active oxygen in the material, reduce the number of unstable active oxygen, and reduce oxygen loss; at the same time, the coating element is coated on the surface of the material. On the one hand, the coating agent can suppress the irreversible phase change of the material, improve the surface performance of the material, and increase the diffusion rate of sodium ions, and further improve the rate performance of the material. On the other hand, the coating layer reduces the contact between the material and the electrolyte, effectively reduces the occurrence of side reactions, and improves the stability and cycle performance of the material, so that the sodium ion battery positive electrode material prepared by the present invention has excellent rate performance and cycle performance at room temperature or low temperature.
[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0016] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0017] The first aspect of the present disclosure provides a method for preparing a positive electrode material for a sodium ion battery, wherein the method comprises: S1, mixing a nickel-iron-manganese precursor, a sodium source and a dopant to obtain a mixed material, and then performing a first sintering treatment to obtain a first powder; S2, mixing the first powder, the carbon and nitrogen source and the first solvent, performing a first heat treatment, and then performing a second sintering treatment to obtain a second powder; S3, mixing the second powder, the coating agent and the second solvent, performing a second heat treatment, and then performing a third sintering treatment to obtain a positive electrode material for a sodium ion battery.
[0018] The coating of carbon elements in the method provided by the present invention can form a uniform conductive network on the surface of the material, so that the rate performance of the material is improved, and can also inhibit the volume change of the material during the charge and discharge process to a certain extent, and improve the stability of the material. At the same time, the nitrogen element contained in the carbon coating layer can stabilize the unstable active oxygen in the material, reduce the amount of unstable active oxygen, and reduce oxygen loss; at the same time, the coating element is coated on the surface of the material. On the one hand, the coating agent can inhibit the irreversible phase change of the material, improve the surface performance of the material, and increase the diffusion rate of sodium ions, and further improve the rate performance of the material. On the other hand, the coating layer reduces the contact between the material and the electrolyte, effectively reduces the occurrence of side reactions, and improves the stability and cycle performance of the material, so that the sodium ion battery positive electrode material prepared by the present invention has excellent rate performance and cycle performance at room temperature or low temperature conditions.
[0019] In a specific embodiment, the total molar ratio of the sodium element in the sodium source to (Ni+Fe+Mn) in the nickel-iron-manganese precursor is (0.90-1.09): 1, preferably (0.95-1.05): 1. In the above embodiment, by controlling the preferred ratio of raw materials to react, it is beneficial to further improve the rate performance, material stability and cycle performance of the positive electrode material of the sodium ion battery.
[0020] In a specific embodiment, the amount of the doping element added to the dopant is 0.4-1.2wt% of the mixed material, preferably 0.6-1.0wt%. In the above embodiment, the introduction of a dopant in a preferred content range during the preparation process can further improve the degree of single crystallization of the prepared sodium ion battery positive electrode material and further reduce the residual alkali on the surface of the material.
[0021] In a specific embodiment, in step S2, the mass ratio of the carbon-nitrogen source to the first powder is (0.001-0.02): 1, preferably (0.004-0.012): 1. In the above embodiment, controlling the preferred ratio of carbon-nitrogen sources can form a more uniform conductive network on the surface of the material, so that the rate performance of the material is effectively improved, and the volume change of the material during the charge and discharge process can be further suppressed, and the stability of the material can be further improved. At the same time, the nitrogen element contained in the carbon coating layer can stabilize the unstable active oxygen in the material, reduce the amount of unstable active oxygen, and further reduce oxygen loss.
[0022] In a specific embodiment, the mass ratio of the added amount of the first solvent to the first powder is (4-8):1, preferably (5-6):1.
[0023] In a specific embodiment, in step S3, the amount of the coating element added to the coating agent is 0.20-1.5wt% of the second powder, preferably 0.50-1.0wt%. In the above embodiment, controlling the preferred content of the coating agent can further inhibit the irreversible phase change of the material, improve the surface properties of the material, effectively increase the diffusion rate of sodium ions, and further improve the rate performance of the material. At the same time, the coating layer reduces the contact between the material and the electrolyte, effectively reduces the occurrence of side reactions, and further improves the stability and cycle performance of the material.
[0024] In a specific embodiment, the mass ratio of the added amount of the second solvent to the second powder is (6-10):1, preferably (7-8):1.
[0025] In a specific embodiment, the sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium oxalate, sodium phosphate, sodium acetate and sodium citrate, preferably one or more of sodium carbonate, sodium bicarbonate and sodium oxalate.
[0026] In a specific embodiment, the carbon-nitrogen source is selected from one or more of polyvinyl pyrrolidone, amides, polyaniline, dopamine and amino acids, preferably one or more of polyvinyl pyrrolidone, amides and dopamine. In the above embodiment, by introducing a carbon-nitrogen source, a uniform conductive network can be formed on the surface of the material, so that the rate performance of the material is improved, and the volume change of the material during the charge and discharge process can be suppressed to a certain extent, and the stability of the material is improved. At the same time, the nitrogen element contained in the carbon coating layer can stabilize the unstable active oxygen in the material, reduce the amount of unstable active oxygen, and reduce oxygen loss.
[0027] In a specific embodiment, the dopant is selected from a compound containing a doping element; the doping element is selected from one or more of Zr, Ti, Mo, Y, Ce, La, Al, W, Nb and Mg, preferably one or more of Zr, Y and Ce.
[0028] In a further embodiment, the dopant is selected from one or more of zirconium oxide, zirconium chloride, basic zirconium carbonate, titanium oxide, titanium chloride, molybdenum oxide, yttrium oxide, cerium oxide, cerium hydroxide, basic cerium carbonate, lanthanum oxide, lanthanum oxalate, lanthanum chloride, aluminum oxide, aluminum chloride, aluminum hydroxide, tungsten oxide, ammonium metatungstate, niobium pentoxide, magnesium oxide, magnesium hydroxide and magnesium carbonate, preferably one or more of zirconium oxide, yttrium oxide and cerium oxide. In the above embodiment, the dopant introduced during the preparation process can effectively improve the single crystal degree of the material, further reduce the residual alkali on the surface of the material, effectively improve the capacity of the material, and enable the material to have excellent rate performance and cycle performance at room temperature or low temperature.
[0029] In a specific embodiment, the coating agent is selected from a compound containing a coating element; the coating element is selected from one or more of Si, Al, Ti, Mg, Ce, La, B, Co and Zr, preferably one or more of Si, Al, La and B.
[0030] In a further embodiment, the coating agent is selected from one or more of sodium silicate, sodium fluorosilicate, aluminum oxide, sodium aluminate, aluminum hydroxide, titanium oxide, magnesium oxide, magnesium hydroxide, magnesium carbonate, cerium oxide, cerium hydroxide, basic cerium carbonate, lanthanum oxide, lanthanum oxalate, boric acid, boron oxide, cobalt hydroxide, cobalt oxalate, cobalt oxide, cobalt carbonate, zirconium oxide and basic zirconium carbonate, preferably one or more of sodium silicate, aluminum oxide, sodium aluminate, lanthanum oxide and boric acid. In the above embodiment, the coating agent introduced during the preparation process can further suppress the irreversible phase change of the material, improve the surface properties of the material, effectively improve the diffusion rate of sodium ions, further improve the rate performance of the material, and at the same time, the coating layer reduces the contact between the material and the electrolyte, effectively reduces the occurrence of side reactions, and further improves the stability and cycle performance of the material.
[0031] In a specific embodiment, the first solvent and the second solvent are selected from anhydrous ethanol and / or isopropanol, respectively, preferably anhydrous ethanol.
[0032] In a specific embodiment, in step S1, the conditions of the first sintering treatment include: in an air or oxygen atmosphere, heating to 500-600°C, preferably 530-580°C, at 2-6°C / min, and then heating to 850-1100°C, preferably 900-1060°C, at 1-4°C / min, and the sintering time is 6-16h, preferably 10-14h.
[0033] In a specific embodiment, in step S2, the conditions of the second sintering treatment include: a sintering temperature of 700-850° C., preferably 750-800° C., and a sintering time of 2-8 hours, preferably 4-6 hours.
[0034] In a specific implementation manner, in step S3, the conditions of the third sintering treatment include: a sintering temperature of 300-700° C., preferably 400-600° C., and a sintering time of 4-10 hours, preferably 6-8 hours.
[0035] In a specific embodiment, the second sintering treatment and the third sintering treatment are performed under an inert atmosphere, and the inert atmosphere is selected from one or more of nitrogen, argon and helium. In the above embodiment, carbonizing the carbon-nitrogen source under an inert atmosphere can form a more uniform conductive network on the surface of the material, so that it is coated on the surface of the material and connects the materials, thereby further improving the rate performance of the material. At the same time, the coating layer reduces the contact between the material and the electrolyte, effectively reducing the occurrence of side reactions, and further improving the stability and cycle performance of the material.
[0036] In a specific embodiment, the first heat treatment is carried out in a reflux device, the temperature of the first heat treatment is 80~120℃, preferably 85~105℃, and the time of the first heat treatment is 0.5~8h, preferably 1~6h; the second heat treatment is carried out in a reflux device, the temperature of the second heat treatment is 80~120℃, preferably 85~105℃, and the time of the second heat treatment is 0.5~8h, preferably 1~6h. In the above embodiment, the reflux method can make the coating more uniformly coated on the surface of the particles, and effectively improve the stability of the coating adhesion; on the other hand, the reflux method is used to coat the elements, which greatly reduces the influence of the air environment on the material, makes it difficult for the sodium in the bulk phase to escape, protects the bulk structure of the material, and reduces the generation of residual alkali on the surface of the material, significantly improves the electrical properties of the material, so that the sodium ion battery positive electrode material prepared in the present disclosure has excellent rate performance and cycle performance at room temperature or low temperature.
[0037] In a specific embodiment, the method further includes, after the first sintering treatment is completed, cooling to 10~30°C and then crushing and screening, the D50 particle size of the first powder is 5~10μm, preferably 6~9μm; after the second sintering treatment is completed, crushing and screening, the D50 particle size of the second powder is 6~9μm, preferably 6.5~8.5μm; after the third sintering treatment is completed, crushing and screening, the D50 particle size of the sodium ion battery positive electrode material is 6~9μm, preferably 6.5~8.5μm.
[0038] In a specific embodiment, the chemical formula of the nickel-iron-manganese precursor is as shown in formula (I): Ni a Fe b Mn c M (1-a-b-c) (OH)2(I), wherein 0.10≤a<1.0, b>0, c>0, 0≤1-abc≤0.15; M is selected from one or more of Mg, Co, Zn, Sr, Al, Cu, Ti, Y, La, Ce, Pr, Nd, V and Cr.
[0039] The second aspect of the present disclosure provides a sodium ion battery positive electrode material prepared by the method described in the first aspect of the present disclosure, wherein the chemical formula of the sodium ion battery positive electrode material is as shown in formula (II): Na β Ni x Fe y Mn z M (1-x-y-z) O2 (II), where 0.90≤β≤1.09, 0.10≤x<1.0, y>0, z>0, 0≤1-xyz≤0.15.
[0040] The sodium ion battery positive electrode material provided by the present invention has high stability, low residual alkali on the material surface, high capacity, and excellent rate performance and cycle performance under normal or low temperature conditions.
[0041] The third aspect of the present disclosure provides use of the sodium ion battery positive electrode material described in the second aspect of the present invention in a sodium ion battery.
[0042] The present invention is further described below by way of examples, but the present invention is not limited thereto. The raw materials used in the examples can be obtained through commercial sources.
[0043] Example 1 a. The nickel-iron-manganese precursor, the sodium source and the dopant are uniformly mixed and dispersed to obtain a mixed material, and then the mixture is heated to 550° C. at 3° C. / min in an air atmosphere, and then heated to 1050° C. at 1.5° C. / min for a first sintering treatment, the sintering time is 13 h, and then the mixture is cooled to 25° C. and then crushed and sieved to obtain a first powder, and the D50 particle size of the first powder is 7.8 μm; Among them, the nickel-cobalt-manganese precursor is Ni 0.36 Fe 0.36 Mn 0.20 Mg 0.08 (OH)2, the sodium source is sodium carbonate, and the dopant is zirconium oxide; the total molar ratio of the sodium source to the nickel iron manganese precursor (Ni+Fe+Mn) is 0.52:1; the amount of Zr added in the dopant is 0.8wt% of the mixed material; b. The first powder, the carbon-nitrogen source and the first solvent are uniformly mixed, placed in a reflux device for a first heat treatment, and then subjected to a second sintering treatment under a nitrogen atmosphere, and then pulverized and sieved to obtain a second powder, wherein the D50 particle size of the second powder is 7.2 μm; Among them, the carbon and nitrogen source is polyvinyl pyrrolidone, the first solvent is anhydrous ethanol; the mass ratio of the carbon and nitrogen source to the first powder is 0.006:1, and the mass ratio of the added amount of the first solvent to the first powder is 5:1; the temperature of the first heat treatment is 90°C and the time is 2h; the temperature of the second sintering treatment is 780°C and the sintering time is 5h; c. The second powder, the coating agent and the second solvent are mixed evenly, placed in a reflux device for a second heat treatment, and then subjected to a third sintering treatment under a nitrogen atmosphere to obtain a sodium ion battery positive electrode material, wherein the D50 particle size of the sodium ion battery positive electrode material is 6.9 μm; Among them, the coating agent is sodium silicate and aluminum oxide, the second solvent is anhydrous ethanol; the mass ratio of the second solvent added to the first powder is 8:1; the amount of the coating element added in sodium silicate is 0.5wt% of the second powder, and the amount of the coating element added in aluminum oxide is 0.25wt% of the second powder; the temperature of the second heat treatment is 90°C, and the time is 3h; the temperature of the third sintering is 580°C, and the sintering time is 7h.
[0044] Example 2 The method of Example 1 is adopted, except that in step b and step c, the first solvent and the second solvent are each isopropanol.
[0045] Example 3 The method of Example 1 is adopted, except that in step b, the carbon and nitrogen source is polyacrylamide.
[0046] Example 4 The method of Example 1 is adopted, except that in step a, the mass ratio of the carbon-nitrogen source to the first powder is 0.0005:1.
[0047] Example 5 The method of Example 1 is adopted, except that in step a, the total molar ratio of the sodium source to the nickel-iron-manganese precursor (Ni+Fe+Mn) is 0.6:1.
[0048] Example 6 The method of Example 1 is adopted, the only difference being that in step b and step c, the temperature of the first heat treatment and the second heat treatment is 70°C.
[0049] Example 7 The method of Example 1 is adopted, except that, in step b, the first powder, the carbon and nitrogen source and the first solvent are mixed evenly and placed in a mechanical ball mill for a first heat treatment.
[0050] Example 8 The method of Example 1 is adopted, the only difference being that in step c, the second powder, the coating agent and the second solvent are mixed evenly and placed in a mechanical ball milling device for a second heat treatment.
[0051] Comparative Example 1 a. The nickel-iron-manganese precursor, the sodium source and the dopant are uniformly mixed and dispersed to obtain a mixed material, and then the temperature is raised to 550° C. at 3° C. / min in an air atmosphere, and then raised to 1050° C. at 1.5° C. / min for sintering. The sintering time is 13 h, and then the mixture is cooled to 25° C. and then crushed and sieved to obtain a first powder. The D50 particle size of the first powder is 7.8 μm; Among them, the nickel-cobalt-manganese precursor is Ni 0.36 Fe 0.36 Mn 0.20 Mg 0.08 (OH)2, the sodium source is sodium carbonate, and the dopant is zirconium oxide; the total molar ratio of the sodium source to the nickel iron manganese precursor (Ni+Fe+Mn) is 0.52:1; the amount of Zr added in the dopant is 0.8wt% of the mixed material; b. The first powder, the coating agent and the organic solvent are uniformly mixed, placed in a reflux device for heat treatment, and then sintered under a nitrogen atmosphere, and then crushed and sieved to obtain a sodium ion battery positive electrode material, wherein the D50 particle size of the sodium ion battery positive electrode material is 6.7 μm; Among them, the organic solvent is anhydrous ethanol, and the coating agent is sodium silicate and aluminum oxide; the mass ratio of the added amount of the organic solvent to the first powder is 8:1; the added amount of the coating element in sodium silicate is 0.5wt% of the first powder, and the added amount of the coating element in aluminum oxide is 0.25wt% of the first powder; the heat treatment temperature is 90°C and the time is 6h; the sintering temperature is 580°C and the sintering time is 7h.
[0052] Comparative Example 2 The method of Example 1 is adopted, except that step c is not performed.
[0053] Test Case The sodium ion battery positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were tested as follows: The particle size of the prepared product was tested using a Malvern particle size analyzer (equipment model: Malvern 3000).
[0054] The electrochemical properties of the sodium ion battery positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were tested as follows: the sodium ion battery positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were mixed with conductive carbon black and binder PVDF in a mass ratio of 80:10:10, and then NMP (N-methyl-pyrrolidone) was added and mixed thoroughly to obtain a slurry of a certain viscosity; the obtained slurry was evenly coated on an aluminum foil, placed in a vacuum drying oven and dried at 110°C for 2h, and after drying, it was pressed with a tablet press, and the pressed electrode sheet was punched into a circular electrode sheet with a diameter of 14mm, and placed in a vacuum drying oven and dried at 100°C for 2h; in an argon-protected glove box, Celgard 2400 membrane was used as a diaphragm, a metal sodium sheet was used as a negative electrode, and 1mol·L -1 NaClO4 / EC+DEC (volume ratio 1:1) was used as the electrolyte to assemble button batteries. The assembled batteries were charged and discharged at the same rate on a blue battery tester at temperatures of 25±1℃ and -20±1℃, respectively, and the test voltage range was 2.5~4.1V.
[0055] The electrochemical cycle performance test instrument is a blue electric tester, and the equipment model is CT3001A.
[0056] Table 1
[0057] According to the test results in Table 1, it can be seen that the sodium ion battery positive electrode material prepared by the method provided by the present invention has high material stability compared with the comparative example, can maintain a high discharge specific capacity at both 25°C and -20°C, and has a higher capacity retention rate after 100 cycles at 1.0C, and can achieve excellent rate performance and cycle performance at both room temperature and low temperature conditions.
[0058] By comparing Example 4 with Example 1, it can be seen that controlling the amount of carbon-nitrogen source within the preferred range of the present application can form a more uniform conductive network on the surface of the material, so that the rate performance of the material is effectively improved, and can further inhibit the volume change of the material during the charge and discharge process, further improve the stability of the material. At the same time, the nitrogen element contained in the carbon coating layer can stabilize the unstable active oxygen in the material, reduce the amount of unstable active oxygen, and further reduce oxygen loss, so that the prepared material has a higher discharge specific capacity and capacity retention rate, and has excellent rate performance and cycle performance at room temperature or low temperature conditions.
[0059] By comparing Example 5 with Example 1, it can be seen that by controlling the preferred ratio of raw materials to react, the rate performance, material stability and cycle performance of the sodium ion battery positive electrode material can be further improved.
[0060] By comparing Examples 7 and 8 with Example 1, it can be seen that the reflux method can make the coating more evenly coated on the particle surface, and can effectively improve the stability of the coating adhesion; on the other hand, the reflux method is used to coat the elements, which greatly reduces the impact of the air environment on the material, making it difficult for the sodium in the bulk phase to escape, protecting the bulk structure of the material, and reducing the generation of residual alkali on the surface of the material, significantly improving the electrical properties of the material, so that the sodium ion battery positive electrode material prepared in the present disclosure has excellent rate performance and cycle performance at room temperature or low temperature conditions.
[0061] By comparing Comparative Example 1 with Example 1, it can be seen that since no carbon and nitrogen source is added, more defects are easily generated on the surface of the material after sintering, and the morphology is uneven and incomplete, resulting in poor rate performance of the material; and the volume change of the material during the charge and discharge process cannot be effectively suppressed, and the amount of unstable active oxygen increases, resulting in poor material stability, so that the prepared material has a low discharge specific capacity, and the 1.0C discharge specific capacity at 25°C and -20°C and the capacity retention rate after 100 cycles at 1.0C are significantly lower than those of Examples 1 to 8.
[0062] By comparing Comparative Example 2 with Example 1, it can be seen that since step c is not performed, there is no coating agent to repair and protect the surface of the material, the direct contact between the material and the electrolyte cannot be effectively reduced, the side reaction is serious, and the irreversible phase change of the material cannot be suppressed, resulting in poor interface stability of the material, which in turn leads to poor internal structural stability of the material, reduced diffusion rate of sodium ions, poor rate performance, and low discharge specific capacity. The 1.0C discharge specific capacity at 25°C and -20°C and the capacity retention rate after 100 cycles at 1.0C are significantly lower than those of Examples 1 to 8.
[0063] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0064] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0065] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, wherein: The method includes: S1, mixing a nickel-iron-manganese precursor, a sodium source and a dopant to obtain a mixed material, and then performing a first sintering treatment to obtain a first powder; S2, mixing the first powder, the carbon and nitrogen source and the first solvent, performing a first heat treatment, and then performing a second sintering treatment to obtain a second powder; S3, mixing the second powder, the coating agent and the second solvent, performing a second heat treatment, and then performing a third sintering treatment to obtain a positive electrode material for a sodium ion battery.
2. The method according to claim 1, wherein: In step S1, the total molar ratio of the sodium element in the sodium source to (Ni+Fe+Mn) in the nickel-iron-manganese precursor is (0.90-1.09): 1; The amount of the doping element added in the dopant is 0.4-1.2wt% of the mixed material.
3. The method according to claim 1, wherein: In step S2, the mass ratio of the carbon-nitrogen source to the first powder is (0.001-0.02): 1; The mass ratio of the added amount of the first solvent to the first powder is (4-8):
1.
4. The method according to claim 1, wherein: In step S3, the amount of the coating element added to the coating agent is 0.20-1.5wt% of the second powder; The mass ratio of the added amount of the second solvent to the second powder is (6-10):
1.
5. The method according to claim 1, wherein: The sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium oxalate, sodium phosphate, sodium acetate and sodium citrate; The carbon and nitrogen source is selected from one or more of polyvinyl pyrrolidone, amides, polyaniline, dopamine and amino acids; The dopant is selected from a compound containing a doping element; the doping element is selected from one or more of Zr, Ti, Mo, Y, Ce, La, Al, W, Nb and Mg; The coating agent is selected from a compound containing a coating element; the coating element is selected from one or more of Si, Al, Ti, Mg, Ce, La, B, Co and Zr; The first solvent and the second solvent are selected from anhydrous ethanol and / or isopropanol, respectively.
6. The method according to claim 1, wherein: In step S1, the conditions of the first sintering treatment include: in an air or oxygen atmosphere, heating to 500-600°C at 2-6°C / min, then heating to 850-1100°C at 1-4°C / min, and sintering time is 6-16h; The conditions of the second sintering treatment include: a sintering temperature of 700-850° C. and a sintering time of 2-8 hours; The conditions of the third sintering treatment include: a sintering temperature of 300-700° C. and a sintering time of 4-10 hours; The second sintering process and the third sintering process are performed under an inert atmosphere, and the inert atmosphere is selected from one or more of nitrogen, argon and helium; The first heat treatment is performed in a reflux device, the temperature of the first heat treatment is 80-120° C., and the time of the first heat treatment is 0.5-8 hours; The second heat treatment is performed in a reflux device, the second heat treatment temperature is 80-120° C., and the second heat treatment time is 0.5-8 hours.
7. The method according to claim 1, wherein: The method further comprises, after the first sintering treatment is completed, cooling to 10-30° C. and then crushing and screening, wherein the D50 particle size of the first powder is 5-10 μm; After the second sintering process is completed, the second powder is crushed and sieved, and the D50 particle size of the second powder is 6-9 μm; After the third sintering process is completed, the material is crushed and sieved, and the D50 particle size of the sodium ion battery positive electrode material is 6-9 μm.
8. The method according to claim 1, wherein: The chemical formula of the nickel-iron-manganese precursor is shown in formula (I): Ni a Fe b Mn c M (1-a-b-c) (OH)2(I), where 0.10≤a<1.0, b>0, c>0, 0≤1-abc≤0.15; M is selected from one or more of Mg, Co, Zn, Sr, Al, Cu, Ti, Y, La, Ce, Pr, Nd, V and Cr.
9. A sodium ion battery positive electrode material prepared by the method according to any one of claims 1 to 8, wherein: The chemical formula of the sodium ion battery positive electrode material is shown in formula (II): Na β Ni x Fe y Mn z M (1-x-y-z) O2 (II), where 0.90≤β≤1.09, 0.10≤x<1.0, y>0, z>0, 0≤1-xyz≤0.
15.
10. Use of the sodium ion battery positive electrode material according to claim 9 in a sodium ion battery.